Cross-Protection Between Group B Arboviruses: Resistance in Mice to Japanese B Encephalitis and St. Louis Encephalitis Viruses Induced by Dengue Virus Immunization - Tarr, G. Crissman (1974)
Albino Swiss mice, immunized with any of several types and strains of dengue viruses, were afforded substantial protection against peripheral Japanese B encephalitis or St. Louis encephalitis virus challenge. Dengue-2 (New Guinea “C”)-immunized mice showed, 10 and 20 weeks after immunization, undiminished resistance with concomitant cyclophosphamide treatment and virus challenge. Examination of the effects of immunization on Japanese B encephalitis virus pathogenesis, after virus challenge with concomitant cyclophosphamide treatment, indicated that protection was associated with decreased viremia and virtually no virus replication in the brain as compared with controls. These effects could be demonstrated before detection of any neutralizing antibody to the challenge virus. From the applied aspect, the data support the hypothesis, based on epidemiological evidence and experiments in hamsters, that prior exposure of man to dengue viruses can confer some degree of protection against Japanese B encephalitis or St. Louis encephalitis disease.